Characterization of patients operated on with a diagnosis of skin cancer over a period of 5 years - Royland Bejerano DurÃ¡n; Alejandra Armada Capote (Revista Cubana de Medicina Militar)
Introduction: Skin cancer is one of the most common types of cancer in the world, and it is estimated that the risk of developing it increases from 1 to 5 throughout life. Its incidence has increased considerably in recent decades. Objective: To characterize the patients operated with skin cancer in the minor outpatient surgery clinic. Methods: A cross-sectional descriptive observational study was conducted in the population attended in the outpatient minor surgery consultation belonging to the Lawton Teaching Polyclinic, located in Diez de Octubre municipality of the province of Havana between the years 2018 and 2022. The following variables were used: sex, age, skin complexion, lesion location and histological type. Frequency analysis was performed. Results: A predominance of females was observed with 57.22%, predominating between the ages of 65 - 76 years of age, mostly of white complexion. There was an increase in the incidence during the year 2021 with 29%. The most frequent location was on the face with 27.84% of the total. The definitive diagnosis according to the biopsy results was solid basal carcinoma with 36.69%. Conclusions: In the series of cases studied, the female sex, the elderly, white skin predominate, and solid basal carcinoma is more frequently present.